2019
DOI: 10.31234/osf.io/q8bju
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bilingual toddlers' comprehension of mixed sentences is asymmetrical across their two languages

Abstract: In bilingual language environments, infants and toddlers listen to two separate languages during the same key years that monolingual children listen to just one and bilinguals rarely learn each of their two languages at the same rate. Learning to understand language requires them to cope with challenges not found in monolingual input, notably the use of two languages within the same utterance (e.g., Do you like the perro? or ¿Te gusta el doggy?). For bilinguals of all ages, switching between two languages can … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 52 publications
3
18
0
Order By: Relevance
“…Our findings show that infants can discriminate their languages at the single-word level when the switch is embedded in a sentence, adding to the suite of perceptual skills that bilingual infants bring to the task of language discrimination and separation. These results are consistent with prior literature testing bilingual 18-to 30-month-old toddlers' comprehension of language switching in an eye tracking task (Byers-Heinlein et al, 2017;Potter et al, , 2018. Theories of bilingual acquisition posit that successful bilingual acquisition relies on infants' ability to discriminate their languages and track each language separately (Curtin et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings show that infants can discriminate their languages at the single-word level when the switch is embedded in a sentence, adding to the suite of perceptual skills that bilingual infants bring to the task of language discrimination and separation. These results are consistent with prior literature testing bilingual 18-to 30-month-old toddlers' comprehension of language switching in an eye tracking task (Byers-Heinlein et al, 2017;Potter et al, , 2018. Theories of bilingual acquisition posit that successful bilingual acquisition relies on infants' ability to discriminate their languages and track each language separately (Curtin et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…In an eye-tracking study (Byers-Heinlein, Morin-FINE-TUNING LANGUAGE DISCRIMINATION 6 Lessard, & Lew-Williams, 2017), 20-month-olds looked less at a target image when the target word was language-switched ("Look at the chien") compared to when the target word was of the same language ("Look at the dog"). Similar results were found for English-Spanish bilingual 18to 30-month-olds (Potter, Fourakis, Byers-Heinlein, & Lew-Williams, 2019;Potter, Fourakis, Morin-Lessard, Byers-Heinlein, & Lew-Williams, 2018). Additional evidence for detection of language-switched words comes from a study of English-Welsh bilingual 2-to 3-year-olds' event-related potentials (Kuipers & Thierry, 2012).…”
Section: Fine-tuning Language Discriminationsupporting
confidence: 66%
See 1 more Smart Citation
“…In a looking-while-listening task, Potter et al (2019) measured how bilingual English-Spanish children aged 1;6-2;6 processed words in their dominant and non-dominant languages where language dominance and exposure were quantified via a background questionnaire. During the task, the children recognized both English and Spanish words embedded in sentences in their non-dominant language but when the words were embedded in sentences in the dominant language, they only recognized the dominant language words.…”
Section: Dual Language Exposure Predicts Learning Outcomesmentioning
confidence: 99%
“…In particular, studies have shown that the amount of child-directed speech (CDS) that children are exposed to during infancy and childhood has meaningful downstream effects on their language development (Hurtado et al 2008;Mahr & Edwards 2018;Newman et al 2016;Ramírez-Esparza et al 2017;Rowe 2008;2012;Weisleder & Fernald 2013). Similarly, differences in bilingual language exposure predict differences in infants' and children's speech processing, speech production, and vocabulary development, suggesting that the amount of bilingual children's exposure to each of their languages explains meaningful variability in their language development (Bijeljac-Babic et al 2012;Byers-Heinlein 2013;Carbajal & Peperkamp 2019;Marchman et al 2017;Orena et al 2020;Pearson et al 1997;Place & Hoff 2011;2016;Potter et al 2019;Unsworth et al 2018;cf. Carroll 2017).…”
Section: Introductionmentioning
confidence: 99%